Hydrophobic proteins secreted into the apoplast may contribute to resistance against Phytophthora infestans in potato - Fernández, María Belén (2012)
During plantepathogen interaction, oomycetes secrete effectors into the plant apoplast where they interact with host resistance proteins, which are accumulated after wounding or infection. Previous studies showed that the expression profile of pathogenesis related proteins is proportional to the resistance of different cultivars toward Phytophthora infestans infection. The aim of this work was to analyze the expression pattern of apoplastic hydrophobic proteins (AHPs), after 24 h of wounding or infection, in tubers from two potato cultivars with different resistance to P. infestans, Spunta (susceptible) and Innovator (resistant). Intercellular washing fluid (IWF) was extracted from tubers and chromatographed into a PepRPC HR5-5 column in FPLC eluted with a linear gradient of 75% acetonitrile. Then, AHPs were analyzed by SDS-PAGE and identified by MALDI-TOF-MS. Innovator cv. showed a higher basal AHP content compared to Spunta cv. In the latter, infection induced accumulation of patatins and protease inhibitors (PIs), whereas in Innovator cv. no changes in PIs accumulation were observed. In response to P. infestans infection, lipoxygenase, enolase, annexin p34 and glutarredoxin/ cyclophilin were accumulated in both cultivars. These results suggest that the AHPs content may be related to the protection against the oomycete and with the degree of potato resistance to pathogens. Additionally, a considerable number of the proteins putatively identified lacked the signal peptide and, being SecretomeP positive, suggest unconventional protein secretion.